The Role of the School Committee in the Implementation of School-Based Management - Paula Agustina Laka; Nani Mediatati (STAI Miftahul Ula Nganjuk, 2024)
This research aims to determine the role of the school committee in implementing school-based management at SMK Negeri 2 Salatiga. This research uses a qualitative descriptive approach with data collection using observation, interviews and documentation methods. Meanwhile, the analysis uses qualitative descriptive analysis techniques based on data obtained in writing and orally from informants. Data validity using triangulation techniques. The research subjects/informants were committee administrators, school principals and teachers at SMK Negeri 2 Salatiga. The research results show that the role of the school committee in implementing school-based management, namely as an advisory body, supporting body, controlling body and liaison body is not optimal. This is caused by a lack of communication and coordination between the school committee and its members, a lack of coordination and communication between the head of the school committee and the school and a lack of understanding of the role of the school committee..